The roles of NADPH oxidase and PKC pathways in the modulation of GLP-1 induced-vasorelaxation in diabetic rat aorta - Ahmed, Solav Sabir Ali; Hussein, Ridha Hassan (Sulaimani Journal for Pure and Applied Sciences, 2023)
A hormone of theincretin system known as glucagon-like peptide-1 (GLP-1) is important for a number of glucoregulatory functions. This study aimed to investigate the effect of inhibitors on the vasorelaxant response of GLP-1 in T1D rats. A single subcutaneous injection of 50 mg/kg of streptozotocin (STZ) was used to develop diabetes mellitus. Eighty aorticrings from twenty male albino rats were prepared. An Automatic Organ Bath was used. In our study, apocynin increased vascular response to GLP- 1 in the non-diabetic group with (Emax:72.40±0.350) and (pD2: - 9.923±0.444). Ininduced diabetes, the NADPH oxidase inhibitor decreased GLP-1 vasodilatation property with (Emax; 68.91±2.002) and (pD2: -9.480±0.138). The results show that bisindolylmaleimide IX (RO31-8220) has an increased effect on GLP-1 vasodilation in non-diabetic groups with (Emax:88.45±38.18) and (pD2: - 10.81±0.281). While in induced diabetic rat’s vascular relaxation of GLP-1 decreased with (Emax: 77.73±2.801) and (pD2: - 10.28±0.203). The data analysis demonstrated that rotenone with (Emax: 63.69±35.10) (pD2: - 9.612±0.246), and in diabetic rats with (Emax:69.98±22.94) and (pD2: -9.612±0.246). In our study oxypurinol with (Emax: 82.16±16.10) and (pD2: - 9.434±0.443), and in diabetic rats with (Emax: 58.03±8.350) and (pD2: -9.612±0.246). We concluded that inhibitors could increase the vasorelaxant response of GLP-1 in non-diabetic rats, while this vasorelaxant response of GLP-1 diminished in diabetic-induced rats
Keywords: NADPH oxidase; PKC pathways; GLP1; vasorelaxation; diabetic rat aorta